1993
DOI: 10.1056/nejm199312303292703
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Insulin Secretory Dysfunction as Precursors of Non-Insulin-Dependent Diabetes Mellitus: Prospective Studies of Pima Indians

Abstract: Insulin resistance is a major risk factor for the development of NIDDM: A low acute insulin response to glucose is an additional but weaker risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
976
3
27

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,381 publications
(1,038 citation statements)
references
References 27 publications
32
976
3
27
Order By: Relevance
“…However, impaired pancreatic beta cell function is an essential element in the development of abnormal glucose tolerance. Indeed, altered beta cell function is a known predisposing factor for type 2 diabetes [4][5][6][7][8], while other studies have found that insulin insensitivity and abnormal beta cell function are independent predictors [9][10][11]. A major problem until now has been the lack of detailed information about the specific abnormalities of beta cell function that predispose to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, impaired pancreatic beta cell function is an essential element in the development of abnormal glucose tolerance. Indeed, altered beta cell function is a known predisposing factor for type 2 diabetes [4][5][6][7][8], while other studies have found that insulin insensitivity and abnormal beta cell function are independent predictors [9][10][11]. A major problem until now has been the lack of detailed information about the specific abnormalities of beta cell function that predispose to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is a well-established risk factor for the development of T2DM [21]. Obesity increases insulin resistance and is associated with elevated cardiovascular risk factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glucose and insulin concentrations were measured in blood samples drawn before glucose ingestion and at 30, 60, 120 and 180 min thereafter. Insulin action was measured at physiologic and supraphysiologic insulin concentrations during a two-step hyperinsulinaemic-euglycaemic glucose clamp [2]. After an overnight fast, a primed continuous intravenous insulin infusion was administered for 100 min at a constant rate of 40 mU·m -2 body surface area·minute -1 (low dose), followed by a second insulin infusion for 100 min at 400 mU·m -2 ·minute -1 (high dose).…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance, characterized as decreased insulin action on glucose uptake and metabolism, is a major predictor of Type II diabetes independent of obesity in Pima Indians of Arizona [2] who have a high prevalence of the disease [3]. Under physiological conditions, insulin-stimulated glucose metabolism occurs mainly in skeletal muscle (>80%) and adipose (~5-10%) tissues [4].…”
mentioning
confidence: 99%